Using the JaCaMo framework to develop a SMA for the MAPC 2012 “Agents on Mars” scenario - Franco, Mariana Ramos; Sichman, Jaime Simão (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
This paper describes the architecture and core ideas of the Multi-Agent System created by the LTI-USP team which participated in the 2012 edition of the Multi-Agent Programming Contest (MAPC 2012). The contest scenario represented a coordinated exploration on Mars. The team organization was based on the Moise organisational model, and its implementation used the JaCaMo multi-agent framework.